Revoking of Farm Laws: A Setback or a Step in the Right Direction - Dr. Pankaj Bala Srivastava (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Repealing the three recent agricultural reform Acts, popularly known as Farm laws, by the Union government of India was a failure or not.Are repealed acts worthy of a reanalysis or buried in past pages? This research paper elucidates that there is no such thing as failure, only a lesson for the future. The paper focuses on different shades of agrarian crisis, the history of agricultural reform laws in independent India, analysis of agricultural reform policies through these Acts & reasons for repealing these Acts. This paper also highlights that a yearlong protest against these Acts caused the death of hundreds of protestors. The paper argues that an appropriate new policy needs to be evolved urgently to safeguard that farming activity becomes viable and the socio-economic condition of farmers is enhanced on a sustainable basis. Keywords: Agricultural Reform Act, Agrarian Crises, Farmer’s, Protest, Farmer’s distress, Samyukta Kisan Morcha, Repeal of Acts